Efektivitas Pemanfaatan Lahan Rawa untuk Mendukung Ketahanan Pangan Nasional melalui Ekspansi Pertanian Padi di Kabupaten Merauke: Studi Kasus Implementasi Program Pemerintah - Chalvyn Silasa Pakidi; Tita Kartika Dewi (CV. Global Cendekia Inti, 2026)
Utilizing swampland as a source of food production is a crucial strategy for supporting national food security amidst limited productive agricultural land and the increasing pressures of climate change. This study aims to analyze the effectiveness of swampland utilization in supporting food security through the implementation of a rice farming expansion program in Merauke Regency, as well as to identify supporting and inhibiting factors in the governance of these resources. This research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, field observations, and documentation studies, which were then analyzed using thematic analysis based on the perspectives of public policy implementation and natural resource governance. The results indicate that swampland utilization in Merauke has strategic potential in supporting national food production, but its implementation effectiveness remains suboptimal. This is influenced by limited infrastructure, the complexity of swampland characteristics, and weak institutional integration and local community participation. Furthermore, the dominance of a top-down approach in policy implementation also impacts program effectiveness at the local level. This study confirms that the success of swampland development is determined not only by technical aspects of agriculture but also by the quality of governance and multi-stakeholder synergy. These findings have important implications for strengthening sustainable swamp ecosystem-based food security policies.